2022
DOI: 10.1101/2022.03.09.22272131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parkinson’s disease causality and heterogeneity: a proteogenomic view

Abstract: Pathogenesis and clinical heterogeneity in Parkinson's disease (PD) have been evaluated from genetic, pathological, and clinical perspective. Technology allowing for high-throughput proteomic analyses in cerebrospinal fluid (CSF) has opened new opportunities to scrutinize this heterogeneity. This is to date the most comprehensive proteomics profiling in CSF of PD patients and controls, both in terms of subjects (n=1103) and proteins (n=4135). Combining CSF aptamer-based proteomics with genetics across all samp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Further, we have shown that non-genetic PD-associated CSF proteomic signatures were correlated with several baseline clinical parameters and CSF biomarkers, and were robustly linked to subsequent motor and cognitive decline in PD, regardless of genetic or non-genetic PD. In conjunction with the findings of an article related to ours, 33 this study provides the most comprehensive proteomic profiling of PD to date. Furthermore, to our knowledge, this is the first study to successfully develop a measure that accurately captures non-genetic PD-associated CSF proteomic signatures and to demonstrate its robust association with the progression of motor and cognitive symptoms of PD, collectively indicating that the CSF proteome encodes information important for both the onset and progression of PD.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Further, we have shown that non-genetic PD-associated CSF proteomic signatures were correlated with several baseline clinical parameters and CSF biomarkers, and were robustly linked to subsequent motor and cognitive decline in PD, regardless of genetic or non-genetic PD. In conjunction with the findings of an article related to ours, 33 this study provides the most comprehensive proteomic profiling of PD to date. Furthermore, to our knowledge, this is the first study to successfully develop a measure that accurately captures non-genetic PD-associated CSF proteomic signatures and to demonstrate its robust association with the progression of motor and cognitive symptoms of PD, collectively indicating that the CSF proteome encodes information important for both the onset and progression of PD.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, it should be mentioned that in an article related to ours, 33 it was found that the most differentially expressed proteins in GBA1 -PD, LRRK2 -PD, and non-genetic PD differed from each other. Therefore, at first, we did not expect to observe that CSF proteomic signatures associated with non-genetic PD also existed in patients with GBA1 -PD, LRRK2 -PD, and SNCA -PD.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations